Novel Lethal Clostridial Infection in Florida Manatees (Trichechus manatus latirostris): Cause of the 2013 Unusual Mortality Event in the Indian River Lagoon - Landsberg, Jan H.; Tabuchi, Maki; Rotstein, David S.; Subramaniam, Kuttichantran; Rodrigues, Thais C. S.; Waltzek, Thomas B.; Stacy, Nicole I.; Wilson, Patrick W.; Kiryu, Yasunari; Uzal, Francisco A.; de Wit, Martine (Frontiers in Marine Science, 2022)
The Indian River Lagoon (IRL) on Florida’s east coast is a biologically diverse estuary and an important habitat to the threatened Florida manatee (Trichechus manatus latirostris). An unusual mortality event (UME) was declared by the Working Group on Marine Mammal Unusual Mortality Events in 2013 after a marked increase in manatee deaths in the IRL of an unknown cause. This UME followed a dramatic reduction of seagrass coverage in the IRL due to chronic non-toxic phytoplankton blooms, with a resultant ecosystem shift to mixed macroalgal dominance. At least 199 manatee deaths fitting the UME case definition were documented in and adjacent to the IRL during 2012–2019; mortality was highest in 2013, when 111 of these deaths were documented. The case definition included carcasses in good nutritional condition, with multiorgan congestion or wet lungs consistent with drowning without trauma. The gastrointestinal compartments of manatee carcasses were filled with diverse macroalga species, and the contents were notably more fluid than usual. Gross intestinal findings included blebbing to segmental thickening of the wall. Microscopic lesions were primarily intestinal, including necrosis, edema, hemorrhage, mucosa-associated lymphoid changes, and inflammation, sometimes associated with Gram-positive bacterial rods. A multidisciplinary approach of environmental and carcass sampling found no causative evidence through tests for micro- and macroalgal biotoxins, trace metals, general toxin screening, or vitreum biochemistry. Microbiological, cytological, immunohistochemical, and molecular analyses of Clostridiales from intestinal samples identified Clostridioides difficile toxin A, toxins A/B and toxin A gene; Paeniclostridium sordellii lethal gene (and other potential virulence factors from a sequenced strain); and Clostridium perfringens alpha and epsilon toxin genes. The results from this 8 year-long investigation are indicative that the cause of death in this manatee UME was associated with clostridial infection, initiated by a shift to a predominantly macroalgal diet.